DESKRIPSI KETERAMPILAN PROSES SAINS SISWA KELAS XI IPA PADA MATERI TITRASI ASAM BASA - Sitanggang, Tiomora; Melati, Husna Amalya; Sartika, Rody Putra (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research was done with aimed to provide an overview of the science process skills of XI IPA grade students of SMAK Abdi Wacana on acid base titration material. The method of this research is a descriptive research. The technique used is measurement techniques and direct communication techniques by using instruments in the form of assessment sheets of science process skills and interview guidelines. The subjects in this study were 20 students of class XI IPA. The results obtained show that the average value of students in classifying is 78% in the highly skilled category. The average score of students in observing, measuring and interpreting data in a row is 60%, 68%, 68% in the skilled category. The average score of students in communicating and concluding successively was 48% and 45% in the less skilled category.Keyword: Science Process Skills, Acid Base Titrations